2017
DOI: 10.1159/000480415
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 Gene-Modified Dendritic Cell-Induced Type 1 Regulatory T Cells Induce Transplant-Tolerance and Impede Graft Versus Host Disease After Allogeneic Stem Cell Transplantation

Abstract: Background/Aims: Tr1 cells can induce peripheral tolerance to self- and foreign antigens, and have been developed as a therapeutic tool for the induction of tolerance to transplanted tissue. We explored the feasibility of generating Tr1 cells by using IL-10 gene-modified recipient DCs (DCLV-IL-10) to stimulate donor naive CD4+ T cells. We also investigated some biological properties of Tr1 cells. Methods: DCLV-IL-10 were generated through DCs transduced with a lentivirus vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…Previously, it was indicated that allogeneic CD4 + T-cells, including Tregs, are closely related to HSCs [10]. Tregs play a significant role in inducing peripheral tolerance to self and foreign antigens [39]. As previously reported, the xenograft survival was longer in CD4+ T-cell-depleted mice, in contrast to in CD4+ T-cell mice [40].…”
Section: /Cd8mentioning
confidence: 77%
“…Previously, it was indicated that allogeneic CD4 + T-cells, including Tregs, are closely related to HSCs [10]. Tregs play a significant role in inducing peripheral tolerance to self and foreign antigens [39]. As previously reported, the xenograft survival was longer in CD4+ T-cell-depleted mice, in contrast to in CD4+ T-cell mice [40].…”
Section: /Cd8mentioning
confidence: 77%
“…Anti‐inflammatory and immunosuppressive factors such as IL‐10, TGF‐β1, FasL and vitamin D3 metabolites produced by genetic modification inhibited the expression of costimulatory molecules and enhanced the tolerogenic potential of DCs to block their maturation and maintain them at the immature stage . Gene‐modified DCs can induce regulatory T cells and promote transplant‐tolerance after allogeneic transplantation . The current study manipulated imDCs to enhance immune tolerance by two mechanisms: suppressing the expression of costimulatory molecules by overexpressing IL‐10; and promoting antigen‐specific T‐cell apoptosis by overexpressing FasL.…”
Section: Discussionmentioning
confidence: 93%
“…The results demonstrate that nasal administration of EBI can induce IL‐10‒expressing DCs; these DCs are CD11c + CD25 + . Because IL‐10‒producing DCs have immune‐tolerogenic properties, this fraction of DCs may be TolDCs.…”
Section: Resultsmentioning
confidence: 99%